SYSTEM FOR ORGANIZING CONTINUOUS TEACHING PRACTICE IN PRIMARY SCHOOL - Sadulloyeva Mahfuza Gaybulloyevna (Western European Studies, 2024)
now we live in the modern country. Our education of the national primary education system places increased demands on the quality of training of modern teachers, which consists not only in the selection of the optimal content of the necessary disciplines implemented in the main and elective parts of the program, but also in the effective organization of various types of continuous teaching practice.
Keywords: continuous teaching practice; system; education; effectiveness